2014
DOI: 10.5194/gmd-7-317-2014
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the performance of the FLake model over two African Great Lakes

Abstract: Abstract. The ability of the one-dimensional lake model FLake to represent the mixolimnion temperatures for tropical conditions was tested for three locations in East Africa: Lake Kivu and Lake Tanganyika's northern and southern basins. Meteorological observations from surrounding automatic weather stations were corrected and used to drive FLake, whereas a comprehensive set of water temperature profiles served to evaluate the model at each site. Careful forcing data correction and model configuration made it p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 89 publications
(74 citation statements)
references
References 43 publications
(46 reference statements)
5
68
1
Order By: Relevance
“…It was found that there is only a little sensitivity to modifications in this parameter for Lake Erie. The same result was found for Lake Kivu in Thiery et al (2014). The bottom sediments module was switched off in all simulations and the zero bottom heat flux condition was adopted.…”
Section: Flake Model and Configurationmentioning
confidence: 56%
See 1 more Smart Citation
“…It was found that there is only a little sensitivity to modifications in this parameter for Lake Erie. The same result was found for Lake Kivu in Thiery et al (2014). The bottom sediments module was switched off in all simulations and the zero bottom heat flux condition was adopted.…”
Section: Flake Model and Configurationmentioning
confidence: 56%
“…The same parametric concept is applied for the ice and snow layers, using linear shape functions . The mixed layer depth is calculated considering the effects of both convective and mechanical mixing, also accounting for volumetric heating which is through the absorption of net shortwave radiation (Thiery et al, 2014). The non-reflected shortwave radiation is absorbed after penetrating the water column in accordance with the Beer-Lambert law (Gordon, 1989).…”
Section: Flake Model and Configurationmentioning
confidence: 99%
“…Its vertical structure consists of an oxic and nutrient-poor mixed layer (seasonally variable depth, up to 70 m), and a permanently anoxic monimolimnion rich in dissolved gases (CH 4 , CO 2 ) and inorganic nutrients (Damas, 1937;Degens et al, 1973;Schmid et al, 2005). Seasonal variations of the vertical position of the oxycline are driven by contrasting hygrometry and long wave radiation between rainy (October-May) and dry (JuneSeptember) seasons (Thiery et al, 2014), the latter being characterized by a deepening of the oxic zone, and an increased input of dissolved gases and inorganic nutrients into the mixed layer , Borges et al, 2011. O 2 concentration was measured with a YSI-proODO probe with a optical O 2 sensor (detection limit is 3 µmol L −1 ), calibrated using air saturated water.…”
Section: Study Site Description and Samplingmentioning
confidence: 99%
“…The highly parameterized model is designed for long-term calculations of lake thermodynamics at low computational costs and with minimum adjustment (Mironov 2008), and was successfully validated for a number of lakes with similar morphological characteristics (Kirillin 2010;Kirillin et al 2012Kirillin et al , 2013Thiery et al 2014). Data input includes the daily sunshine duration and daily means for temperature, wind speed, relative humidity, and cloud cover (data set available since 1951).…”
Section: Monitoring Of Lake Conditions Meteorological Data and Modelingmentioning
confidence: 99%